The Relationship between Leadership, Organizational Culture, and Human Capital in Organizations: Bibliometric - Choirul Anam; Arief Purwanto; Hanif Rani Iswari (Journal of Management Research and Studies, 2023)
Leadership, organisational culture, and human capital have important roles in every organisation. The purpose of this study is to reveal the relationship between leadership, organizational culture, and human capital in organisations with a bibliometric. The bibliometric method is used to provide a complete picture of the development of research related to a particular topic so that researchers can understand the topic at a macro level. Bibliometric studies help identify macro research gaps (sub-sub topics that have not been researched, emerging topic trends). The researcher focused on bibliometric analysis: co-authorship with the first author unit of analysis and co-occurrence with the keyword unit of analysis. The findings show that organisational culture variables, although a minority, still exist in the last 15 years to be researched further. On the other hand, human capital and leadership with emphasis on leadership style can be associated with other variables, such as competence, entrepreneurship, information-communication technology. This research also has limitations, namely in the literature sources obtained, increasing there are still few researchers who review leadership, organisational culture, and human capital.